Juvenile Hyaline Fibromatosis (JHF): A Rare Case with Recurrence - M.V, Rashmi (JCDR Research and Publications (P) Limited, 2014)
Juvenile hyaline fibromatosis (JHF) is a rare autosomal recessive disease. Less than 70 cases of JHF have been reported worldwide and extremely few from India. We present a case of 4-year-old girl who presented with multiple painless nodular masses on the scalp. On fine needle aspiration cytology, a diagnosis of benign spindle cell lesion was provided, the scalp lesions were excised and on histopathology the diagnosis of JHF was made. Retrospectively, the cytology slides were reviewed and the features were consistent with the diagnosis. A diagnosis of JHF was made based on the classical clinical features, Fine Needle Aspiration Cytology (FNAC) findings and the characteristic histopathological features along with a supportive evidence based on special stains. However, the patient had a recurrence within two years. Hence, we present this rare case with recurrence.